2021
DOI: 10.1155/2021/8873389
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis C Viral Infection in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Background. Hepatitis C virus is a highly genetically heterogenous bloodborne pathogen that is responsible for acute and chronic hepatitis. Globally, an estimated 71 million population is chronically infected with this virus from which 399,000 people die every year. Its prevalence is high in Ethiopia and varies from region to region, even among different studies within a region. Methods. Electronic databases, including Science Direct, Medline, HINARI, African Journals Online, TRIP database, African Index Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 94 publications
1
9
0
Order By: Relevance
“…Overall anti-HCV seroprevalence was 1.9% (95% CI: 0.9%, 3.0%), which is considered low endemicity by WHO. 22 , 23 The results were consistent with the results of the previous studies conducted on the general population in the South Omo Zone, 1.9%, 20 the recent pooled national prevalence of 2%, 34 the 2% prevalence reported from Gambella, Ethiopia 18 and 1.4% among community members in southern Ethiopia 19 However, the seroprevalence was less than that of 3.1% of the previous national pooled prevalence, 17 4.3% in previous studies reported from Northwest Ethiopia, 35 3.0% prevalence found in sub-Saharan Africa, 36 , 37 3.4% Africa, 4.8% Somalia, 6.2% Pakistan, 6.5% Cameron, and 11.9% Egypt. 38–42 On the contrary, it is greater than the 1.0% prevalence reported in Gojjam, Ethiopia; 28 0.64% prevalence reported in Nekemite, Ethiopia, 43 0.4% in Iraq, 44 0.3% in Djibouti, 0.9% in Somalia, and 1.0% in Sudan 36 among the general populations.…”
Section: Discussionsupporting
confidence: 90%
“…Overall anti-HCV seroprevalence was 1.9% (95% CI: 0.9%, 3.0%), which is considered low endemicity by WHO. 22 , 23 The results were consistent with the results of the previous studies conducted on the general population in the South Omo Zone, 1.9%, 20 the recent pooled national prevalence of 2%, 34 the 2% prevalence reported from Gambella, Ethiopia 18 and 1.4% among community members in southern Ethiopia 19 However, the seroprevalence was less than that of 3.1% of the previous national pooled prevalence, 17 4.3% in previous studies reported from Northwest Ethiopia, 35 3.0% prevalence found in sub-Saharan Africa, 36 , 37 3.4% Africa, 4.8% Somalia, 6.2% Pakistan, 6.5% Cameron, and 11.9% Egypt. 38–42 On the contrary, it is greater than the 1.0% prevalence reported in Gojjam, Ethiopia; 28 0.64% prevalence reported in Nekemite, Ethiopia, 43 0.4% in Iraq, 44 0.3% in Djibouti, 0.9% in Somalia, and 1.0% in Sudan 36 among the general populations.…”
Section: Discussionsupporting
confidence: 90%
“…Contrarily, the rate of HIV/HCV coinfection in this study is higher than that of studies done in Ethiopia, which revealed a 1.3% rate (Balew et al, 2014). This 4.0% is also higher than the 0.5% for HIV/HCV coinfection among HIV-infected and HIV-naive children in Lagos (Lawal et al, 2020), the 1.7% in Northcentral, Nigeria (Durowaye et al, 2014), the 1.5% in the USA (Schuval et al, 2004), 1.0% was recorded by Aaron et al (2021) in Port Harcourt, Nigeria, the 0.16% prevalence in the southeast of Nigeria (Ikeako et al (2014), 0.5% in Anyigba (Omatola et al, 2019), 0.7% in the southeast (Diwe et al, 2013), 0.8% in Abuja (Agboghoroma & Ukaire, 2020), 0.8% in Osogbo (Oluremi et al (2021), 0.9% reported by Onyekwere and Hameed (2015) and 2.0% in Ethiopia (Deress et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…In a large group of children who were perinatally HIV-positive and were part of a long-term follow-up program, the prevalence of HCV infection in the United States was 1.5%, compared to a rate of 9.6% in China (Schuval et al, 2004; Zhou et al, 2010; Lawal et al, 2020). However, several African nations, such as Tanzania, where a prevalence of 13.8% has been recorded, and Ethiopia, where the prevalence of anti-HCV ranged from 0.0% to 22.0%, have seen a higher incidence of this coinfection (Deress et al, 2021) On the other side, Cote d’ Ivoire in West Africa recorded a prevalence rate of 0.0% (Telatela et al, 2007; Rouet et al, 2008; Riou et al, 2016; Lawal et al, 2020) and in Ivory Coast and Kenya (Puoti et al, 2008; Rouet et al, 2008). Similarly, studies in Port Harcourt, Nigeria, and East Africa found 0.0% prevalence rates for HIV/HCV coinfection (Chakraborty et al, 2003; Okonko et al, 2014; Lawal et al, 2020; Cookey et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings of a number of research, the Hepatitis C Virus is most prevalent in parts of Asia and sub-Saharan Africa. 12 It has been shown that the prevalence of HCV in Europe ranges anywhere from 0.1 to 6%. 20 There has been a recent rise in the incidence of HCV infection in India.…”
Section: Discussionmentioning
confidence: 99%
“…The Hepatitis C virus has an infectious potential that is four times higher than that of the human immunodeficiency virus. 12 The Hepatitis C Virus is the most common cause of chronic liver illness in people who are receiving hemodialysis. 13 When compared to those in other occupations, the prevalence of antibodies against the hepatitis C virus in those working in healthcare is three times greater.…”
Section: Introductionmentioning
confidence: 99%